2006
DOI: 10.1002/hep.21040
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I allelic diversity and progression of fibrosis in patients with chronic hepatitis C

Abstract: Patients infected with HIV-1 who are heterozygous at HLA class I loci present greater variety of antigenic peptides to CD8 ؉ cytotoxic T lymphocytes, slowing progression to AIDS. A similar broad immune response in chronic hepatitis C (CHC) infection could result in greater hepatic injury. Although specific HLA class II alleles may influence outcome in CHC patients, the role of HLA class I heterogeneity is generally less clearly defined. Our aims were to determine whether HLA class I allelic diversity is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 41 publications
1
34
1
2
Order By: Relevance
“…In this study, no statistically significant association was found between different HLA-A and HLA-B antigens and elevated ALT level, HCV viral load, grades of activity or degree of fibrosis except for association between HLA-A9 and low HCV viral load. HLA Class I alleles were not associated with viral load, fibrosis stage, liver inflammation or treatment outcome in Irish and American studies [25,41]. However, in a Taiwanese study [42], patients with chronic HCV infection with HLA alleles (A*34, B*56) have significantly lower viral load than those without these alleles, while those with HLA-B*4001 have significantly higher viral load.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, no statistically significant association was found between different HLA-A and HLA-B antigens and elevated ALT level, HCV viral load, grades of activity or degree of fibrosis except for association between HLA-A9 and low HCV viral load. HLA Class I alleles were not associated with viral load, fibrosis stage, liver inflammation or treatment outcome in Irish and American studies [25,41]. However, in a Taiwanese study [42], patients with chronic HCV infection with HLA alleles (A*34, B*56) have significantly lower viral load than those without these alleles, while those with HLA-B*4001 have significantly higher viral load.…”
Section: Discussionmentioning
confidence: 86%
“…The study population consisted of 670 adults with chronic HCV infection, including 155 with advanced cirrhosis and 237 non-HCV controls. 78 These results suggest that hepatic injury is more likely to be determined by a complex interplay between host, viral and genetic factors. They also suggest while genetic restriction may play an important role in the early phase of infection that determines the outcome, once viral persistence is established specific genetic restrictions of virus-specific CD8 þ T-cell responses may not be of any significant relevance.…”
Section: Role Of Class I Alleles In Hcv Infectionmentioning
confidence: 92%
“…Associations with HLA class Ⅱ genes are reported more often than HLA class I . HLA class I allelic diversity is suggested to have little influence on fibrosis and disease severity associated with chronic HCV infections [53] . HLA class I allele associations: Susceptibility to HCV infections is associated with A*19 in Saudi people [54] and with HLA A*28, A*29, B*14, DR7 in Egyptians [55] .…”
Section: Viral Persistence and Viral Clearancementioning
confidence: 99%